2022
DOI: 10.3390/dj10060106
|View full text |Cite
|
Sign up to set email alerts
|

Association between Periodontitis and COVID-19 Based on Severity Scores of HRCT Chest Scans

Abstract: Background: A relationship between periodontitis and COVID-19 may exist, as highlighted by several hypothetical models. However, the evidence is limited. Hence, the present study was conducted to determine whether an association exists between periodontitis and COVID-19. Methods: A cross-sectional study was carried out with patients diagnosed with COVID-19 who were divided into three groups—mild, moderate, and severe COVID-19—based on the COVID-19 severity score of high-resolution computed tomography (HRCT) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…A total of 22 studies, involving 92,535 patients were included in the present systematic review; [ 22 25 , 27 – 29 , 33 47 ] of these, 12 studies were included in the meta-analysis [ 23 , 25 , 27 , 28 , 33 , 35 , 36 , 40 , 41 , 43 , 44 , 46 , 47 ]. Twelve of these studies were case–control studies, [ 22 25 , 29 , 34 , 35 , 37 , 38 , 42 , 44 , 46 ] three cohort studies, [ 27 , 28 , 39 ] and seven cross-sectional studies [ 33 , 36 , 40 , 41 , 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 studies, involving 92,535 patients were included in the present systematic review; [ 22 25 , 27 – 29 , 33 47 ] of these, 12 studies were included in the meta-analysis [ 23 , 25 , 27 , 28 , 33 , 35 , 36 , 40 , 41 , 43 , 44 , 46 , 47 ]. Twelve of these studies were case–control studies, [ 22 25 , 29 , 34 , 35 , 37 , 38 , 42 , 44 , 46 ] three cohort studies, [ 27 , 28 , 39 ] and seven cross-sectional studies [ 33 , 36 , 40 , 41 , 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies focusing on COVID-19 severity or complications such as assisted ventilation, intensive care admission and deaths report 3 to 36 times higher odds of any COVID-19 complication among periodontally compromised individuals ( 14 16 , 18 , 19 , 38 ) compared to those with healthy periodontium. Despite reporting statistically significant results, the wide confidence intervals indicate low precision due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional ( 12 , 14 , 16 19 ) and prospective ( 13 , 15 ) observational studies report, over three-fold increase in severity of COVID-19 infection (and death) among persons with poor oral health or PD. However, they are limited by either sample size, lack of community level prospective data, or clinically ascertained oral health status.…”
Section: Introductionmentioning
confidence: 99%
“…These included six case-control studies 11,12,22−25 , three cohort studies 26-28 and two crosssectional studies. 5,29 The NOS scores of the Seven studies were ≧ 5, and the scores of the 11 checklist recommend by AHRQ were ≧ 8, which suggested moderate or high quality for the included studies. The basic characteristics of the included literature are shown in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%